On‐ and off‐the‐job embeddedness differentially shape stress‐related reactions to job insecurity - Porter, Caitlin M.; Peltokorpi, Vesa; Allen, David G. (Applied psychology, 2024)
The prevalence of job insecurity is increasing due to technological, geopolitical, and environmental changes worldwide, leading to negative stress‐related reactions and health outcomes for employees and productivity loss for organizations. Despite these consequences, few recommendations exist for how people can effectively cope with perceived job insecurity to mitigate stress‐related reactions. Drawing from resource‐based stress theories, we highlight job embeddedness, which captures contextual resources derived from on‐the‐job and off‐the‐job domains, as a key factor shaping employee's stress‐related reactions to job insecurity. Data collected at three time points over 12 months from 483 employees in various organizations in Japan reveals that on‐the‐job embeddedness exacerbates the positive relationships of job insecurity with both emotional exhaustion and chronic insomnia, whereas off‐the‐job embeddedness mitigates these associations. This study contributes to the literature by identifying off‐the‐job embeddedness as a bundle of contextual resources that helps employees cope with perceived job insecurity and demonstrating the contrasting effects of the two dimensions of embeddedness in shaping health‐related consequences of job insecurity.